Biocatalytically induced surface modification of the tobacco mosaic virus and the bacteriophage M13. Issue 1 (5th December 2018) - Vignali, Valentina; S. Miranda, Barbara; Lodoso-Torrecilla, Irene; van Nisselroy, Cathelijn A. J.; Hoogenberg, Bas-Jan; Dantuma, Sybren; Hollmann, Frank; de Vries, Jan Willem; Warszawik, Eliza M.; Fischer, Rainer; Commandeur, Ulrich; van Rijn, Patrick
Abstract : A one-step laccase induced free radical oxidation of the tobacco mosaic virus and bacteriophage M13 led to acrylate-functionalized viruses with customizable properties. Abstract : Engineered viruses are finding an increasing number of applications in basic, translational research and materials science. Genetic and chemical engineering of capsids represents a key point for tailoring the properties of viral particles, but the synthetic efforts and limits accompanying these processes still hinder their usability. Here, a single-step highly selective biocatalytic functionalization approach is described, providing a general platform for virus–acrylate hybrid particles. The tobacco mosaic virus (TMV) and the bacteriophage M13 have been successfully modified via laccase induced free radical formation on the tyrosine residues through single electron oxidation as the initiating step and the free radicals subsequently react with acrylate-based monomers. This new approach can be extended to other biomolecular assemblies with surface exposed tyrosine residues, when the introduction of new functionalities is desired.